Crea il tuo bot-chimico telegram - Merola, Giovanni; Mancini, Maria Cristina; Alessandroni, Maria Laura (Chimica nella Scuola, 2024)
In the digital age we live in, interactive learning has become a fundamental approach to engaging students effectively and stimulating their interest. Chemistry, with its complex formulas and molecular properties, can be a challenging subject for many students. However, recent advancements in artificial intelligence and the widespread availability of scientific data enable us to harness the potential of messaging bots to create innovative educational tools. A Telegram bot is a software application that operates within the Telegram messaging platform. Bots are designed to automate interactions and provide services to users through text-based chats. In the context of this project, the chemical bot on Telegram is developed with the aim of functioning as an interactive chemistry expert. Users can send questions and requests to the bot via chat, and the bot will respond by providing relevant chemical information. The educational significance of creating a Telegram bot extends beyond students specialized in computer science to include chemistry students. The process of developing a chemical bot involves acquiring cross-disciplinary skills that are valuable in various fields of study. By creating a bot, chemistry students can enhance their understanding of programming concepts and gain practical experience in integrating technology into their domain of study. This project provides a guide on creating a chemical bot using Python code executed on Google Colab. It explores how the bot utilizes the PubChemPy library to retrieve chemical information from the PubChem database. Users can interact with the bot, obtaining answers to basic questions such as retrieving the molecular mass of a compound based on its formula. Through the development of a chemical bot, students can develop critical thinking, problem-solving, and communication skills. Moreover, this innovative approach to studying chemistry fosters a deeper understanding of the subject matter and encourages active engagement with technology.